Pengaruh Partisipasi Anggaran Dan Komitmen Organisasi Terhadap Kinerja Manajerial (Studi Kasus Pada Pusat Penelitian Teh Dan Kina) - Syamsul Amry; Dety Mulyanti (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
The purpose of this study was to determine the effect of budgetary participation and organizational commitment on managerial performance at the Pusat Penelitian Teh dan Kina. The data used in this study are primary data, namely data obtained directly from the source, namely through respondents who filled out questionnaires and used secondary data, namely in the form of supporting data whose sources are from agencies, the internet and the library. This test was carried out using the SPSS program, which included validity tests and reliability tests. The results of this study indicate that budgetary participation and organizational commitment have a positive effect on managerial performance.